2017
DOI: 10.1177/0261927x17704238
|View full text |Cite
|
Sign up to set email alerts
|

Emojis as Tools for Emotion Work: Communicating Affect in Text Messages

Abstract: Emojis are pictures commonly used in texting. The use and type of emojis has increased in recent years; particularly emojis that are not faces, but rather objects. While prior work on emojis of faces suggest their primary purpose is to convey affect, few have researched the communicative purpose of emojis of objects. In the current work, two experiments assess whether emojis of objects also convey affect. Different populations of participants are shown text messages with or without different emojis of objects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 28 publications
2
100
0
2
Order By: Relevance
“…Around the time we started collecting data, the New York Times declared, “The Emoji Have Won the Battle of Words” (Bennett, ). Emojis help signify nonverbal emotions and social context during screen‐based communication (Stark & Crawford, ), even when they only show objects (e.g., Riordan, ). We first tested how similarly people from each culture rated six common emojis.…”
Section: Introductionmentioning
confidence: 99%
“…Around the time we started collecting data, the New York Times declared, “The Emoji Have Won the Battle of Words” (Bennett, ). Emojis help signify nonverbal emotions and social context during screen‐based communication (Stark & Crawford, ), even when they only show objects (e.g., Riordan, ). We first tested how similarly people from each culture rated six common emojis.…”
Section: Introductionmentioning
confidence: 99%
“…Related Work. Linguistic research on emojis has explored various uses of emojis and emoticons, such as marking illocutionary force and communicating affect (e.g., Dresner & Herring (2010), Herring & Dainas (2017), Riordan (2017a)). Not only can emojis perform numerous communicative functions, a specific emoji can be ambiguous in its communicative contribution.…”
mentioning
confidence: 99%
“…Screenshots were inserted into the surveys as images, removing the possibility for cross-platform visual differences of the emojis. A continuous, unnumbered sliding scale (as opposed to an ordinal integer scale) was used to allow for parametric analysis (e.g., Allen & Seaman (2007), Sullivan & Artino (2013), Weissman (2019)). Participants saw only one stimulus and provided one rating; this prohibits using a mixed-effects model for analysis but counteracts in-survey comparison bias in ratings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Emojitracker.com, a website that monitors the emoji use on Twitter in real time, 24 of the top 50 emojis are non-face emojis (at the time accessed by the author on April 10, 2018, at 6:00 pm), implying a widely accepted communicative role of non-face emojis. Indeed, recent research has shown that non-face emojis can serve the two communicative roles of face emojis as well (Kaye et al, 2016;Riordan, 2017aRiordan, & 2017b. For example, it was found that tweets with emojis (either face or non-face) were consistently more positive than those without, indicating that non-face emojis carry emotional information as well (Novak, Smailović, Sluban, & Mozetič, 2015).…”
Section: The Communicative Role Of Emojismentioning
confidence: 99%